PENYELENGGARAAN URUSAN PEMERINTAHAN KONKUREN PADA PEMERINTAHAN DAERAH KABUPATEN SIAK - Maulidiah, Sri; Husnah, Asmaul (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2018)
As explained in Law Number 23 of 2014 that government affairs consist of absolute government affairs, concurrent government affairs and general government affairs. This study aims to analyze the implementation of concurrent government affairs in the local government of Siak Regency. At the regional level the implementation of concurrent government affairs is carried out by regional government elements and Dewan Perwakilan Rakyat Daerah (DPRD). In the implementation of government affairs in the regions, especially in the local government of Siak Regency there are still several problems, namely; the absence of tourism policies from Law Number 23 of 2014 such as Government Regulations related to concurrent government affairs and regional apparatus organizations implementing concurrent affairs was only established in 2017. This study used a Qualitative Approach withtype descriptive explanatory. The informants in this study were the Regional Secretary of Siak Regency, Head of the Education Office, to the Health Office and Head of the Social Service. Based on the results of the study that the nature of the implementation of concurrent government affairs in the local government of Siak Regency is in accordance with the planning, and has achieved the targets set out in the Annual Work Plan of the Siak Regency Regional Government, and all programs and activities in concurrent government affairs are financed through the Siak Regency budget has increased every year, but there are still some obstacles in the implementation of concurrent government affairs in the local government of Siak Regency. The suggestions that the author recommends in implementing concurrent government affairs are; improving facilities and infrastructure in the implementation of concurrent government affairs activities, immediately completing the preparation of the Regional Government RTRW of the Siak Regency.